Ceux Qui Nous Aident a Tenir Debout - Hirtt, Sarah (France, 2012)
Three ex-convicts speak about those who help or have helped them get by. Three portraits, three testimonials, three paths of life.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films